Amidoalkyl Naphthols: Trifluoroacetic Acid (TFA) Catalyzed One-Pot, Multi-Component Synthesis - Kadam, Vinay S.; Khanvilkar, Priyanka R.; Patel, Arun L. (Journal of Applied Solution Chemistry and Modeling, 2013)
Trifluoroacetic acid (TFA) was found as an efficient catalyst for the synthesis of amidoalkyl naphthols from aromatic aldehydes, β-naphthol and acetamide/benzamide under solvent free condition at 80o C. All the synthesized compounds were characterized by IR, 1H NMR and Mass spectra. The advantages of the new method were good yields, short reaction times, simple work-up, inexpensive and easily available catalyst and economical due to absence of solvent. Therefore, this method could be an attractive alternative to existing methods for the synthesis of biologically important amidoalkyl naphthols. <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->